Build-to-Rent and the financialization of rental housing: future research directions. Issue 5 (27th May 2020) - Nethercote, Megan
Abstract: With the expansion of institutional investors into urban rental markets, many cities have witnessed a rise in Build-to-Rent (BtR). This article reviews the financialization of rental housing literature and identifies opportunities for urban housing scholars to progress understandings of BtR through future empirical and theoretical efforts. In particular, it proposes a broadening of the housing research agenda around three analytical entry points. These entry points relate to relatively understudied structural transformations of our urban housing systems implicated in the rise of BtR, namely: (1) the diversification of build-to-sell development models; (2) the evolution of the private rental sector; and (3) labour market–housing market realignments. Comparative inquiry promises to enrich understandings of BtR by revealing how city rental accommodation and tenancies are recalibrated by the investment imperatives of institutional investors and BtR asset shareholders, and with what benefits and at what costs to whom. Such contributions will also provide rich data to progress conceptual efforts to locate BtR within broader processes of housing financialization.